PENINGKATAN KETERAMPILAN MENDENGARKAN CERITA ANAK MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS I SDN 006 BENCAH KELUBI KABUPATEN KAMPAR - Mudawarnis Mudawarnis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low listening skill of class I SDN 006 Bencah Kelubi Kampar. The purpose ofthis research is to improve the listening skill of children's story of grade 1 SDN 006 Bencah Kelubi Kamparthrough the use of audio visual media. This research was conducted at SDN 006 Bencah Kelubi KamparDistrict, The subject of research is the first grade students with the number of students as many as 28 people.The form of research is classroom action research. The research instrument is a test of story listening skills. Theresults of the average score of students' reading skill increased from 66.8 to 72.3 and increased to 73.8 thenincreased to 77.1, and increased again to 83.6. Based on the research results, it can be concluded that the use ofaudio visual media can improve students' listening skills.